INFLUENCE OF PRINCIPAL MANAGEMENT PRACTICES OF TEACHER PROFESSIONAL RECORDS ON STUDENTS’ ACADEMIC PERFORMANCE IN KCSE IN PUBLIC SECONDARY SCHOOLS IN MASHURU SUB-COUNTY - Muasa, Damaris Mwikali; Ogola, Fredrick; Nzioki, Susan (African Journal of Emerging Issues (AJOEI), 2021)
Purpose of the study: The purpose of the study was to determine the influence of principals’ management practices of teacher professional records on students’ academic performance in KCSE in public secondary schools in Mashuru Sub-County. Statement of the problem: According to the records from the office of the Kajiado County Director of Education, the performance of students in KCSE in Mashuru Sub-County has not only been poor but also spiralling downwards. The region has only produced 23 students attaining a grade of C+ in a period of four years. The poor performance calls for a scrutiny of what could be the cause to this status quo. There was therefore need to establish whether despite all efforts put in place, the students’ academic performance in KCSE was still declining. Research Methodology: The study utilized a descriptive research design.The target population consisted of 45 principals, 540 teachers and 585 student leaders. Simple random sampling was employed to select a sample size of 13 principals, 54 teachers and 56 student leaders. Data was collected by use of interview schedule for principals and questionnaires for teachers and student leaders. The collected data was analysed using descriptive statistics which consisted of frequencies and percentages with the help of SPSS version 27. Research Findings: The study established that principal management practice on teacher professional records had some influence on student academic performance in KCSE in public secondary schools. Conclusion: The study concluded that principals’ management practice of teacher professional records influenced students’ academic performance in KCSE as well as the quality and standards of education in public secondary schools in Mashuru Sub-County. Recommendations: The study recommended that the principals and other stakeholders in the education sector should sensitize the teachers on the importance of preparing teachers professional records to the recommended standards and on time. These findings could be used by serving principals to establish the reasons of poor performance in their schools and the corresponding corrective measures. This will also help to improve their professional competence and performance.
Keywords: Principals’ Management Practice; Teacher Professional Records; Students’ Academic Performance in KCSE; Public Secondary Schools